Liana: the stalking strangler? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Best known as Tarzan s preferred means of transport, the twine-like liana may have a negative impact on its rainforest habitat. The role of lianas in forest ecologies has long been underestimated, and these climbing jungle weeds were for long...